The reliability and validity of subjective notational analysis in comparison to global positioning system tracking to assess athlete movement patterns - Dogramac, S. N.; Watsford, M. L.; Murphy, A. J. (The Journal of Strength and Conditioning Research, 2011)
Subjective notational analysis can be used to track players and analyse movement patterns during match-play of team sports such as futsal. The purpose of this study was to establish the validity and reliability of the Event Recorder for subjective notational analysis. A course was designed, replicating ten minutes of futsal match-play movement patterns, where ten participants undertook the course. The course allowed a comparison of data derived from subjective notational analysis, to the known distances of the course, and to GPS data. The study analysed six locomotor activity categories, focusing on total distance covered, total duration of activities and total frequency of activities. The values between the known measurements and the Event Recorder were similar, whereas the majority of significant differences were found between the Event Recorder and GPS values. The reliability of subjective notational analysis was established with all ten participants being analysed on two occasions, as well as analysing five random futsal players twice during match-play. Subjective notational analysis is a valid and reliable method of tracking player movements, and may be a preferred and more effective method than GPS, particularly for indoor sports such as futsal, and field sports where short distances and changes in direction are observed.